Citraan Puisi di Negeri Amplop pada MK Kajian Puisi Mahasiswa Bahasa Indonesia FKIP UNKHAIR - Nada, Anwar; Zulianto, Sugit; Wahab, Justam (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
Imagery is a form of language use that can give a concrete impressions of an object, scene, action, or statement that distinguishes it from abstract expository statements and usually has something to do with symbolism. This is illustrated in the poem "Di Negeri Amplop" by KH. A. Mustofa Bisri which involves 7 elements of poetic imagery. The purpose of this study is (1) to find out how students analyze the image of poetry in the land of KH's envelope. A Mustofa Bisri. (2). To find out the application of poetry learning materials by lecturers. Researchers use descriptive qualitative methods. Data collection techniques include: Observation, Interview, and Documentation. In connection with this, data analysis techniques can be obtained from various sources of books related to poetry. The data analysis techniques data reduction, data display, and verification. The results of this study show that students' ability to analyze poetry imagery is still very low. This is related to the method of application in learning is still conventional. Furthermore, it can be argued that imagery is a style of narration that is widely used in literary writing. The image gives an interesting impression to the poem "Di Negeri Envelope" by KH. A. Mustofa Bisri which involves the 7 elements of imagery. In connection with this, the application of literature learning methods must be varied so that students' analytical skills can be improved.